RELATIONSHIP BETWEEN MANAGEMENT OF FAMILY FUNCTIONS AND MARRIAGE SATISFACTION WITH THE EVENT OF POSTPARTUM BLUES IN POSTPARTUM MOTHERS IN THE WORK AREA OF KRAMATWATU PUBLIC HEALTH CENTER - Ike Puspasari Ayu; Milawati Lusiani; Herna Alifiani; Elfina Yulidar; Nurhayati Nurhayati (AGUSPATI Research Institute, 2022)
The postpartum blues are still considered as something worth considering canceled neglected. Family as a Mother-Against Environment that Protects Mother's Development. The function of the family in providing support and satisfaction in the relationship between husband and wife must be optimized properly because it can improve itself as a wife in her new role as a mother. This study discusses family relationships and marital satisfaction with the incidence of postpartum blues in postpartum mothers in the Puskesmas Kramatwatu. This research was conducted using quantitative methods using cross sectional. The sample in this study was obtained proportionally randomly with 69 randomly selected postpartum mothers. The results of the study stated that there was a relationship between family and postpartum blues (P value = 0.016) and there was no correlation between marital satisfaction and postpartum blues (P value = 0.674). Mothers who improve postpartum blues must be helped by, because the mother's role is very opposed to children's development also in opposing the role of mother in the family.